Ossifying fibroma of the jaw bones in hyperparathyroidism-jaw tumor syndrome: Analysis of 24 cases retrieved from literatures - Hazim Mahmoud Ibrahem (Elsevier, 2020)
Background/purpose: Hyperparathyroidism-jaw tumor syndrome is a rare autosomal dominant disease characterized by parathyroid tumors and ossifying fibroma of the jaw. Disease-causing mutations have been localized in the tumor suppressor gene CDC73. This study is designed to highlight the importance of genetic testing in the diagnosis of ossifying fibroma related to this syndrome. Materials and methods: The Clinical, histopathological, radiographical, familial and genetic features of 24 patients with Hyperparathyroidism-jaw tumor syndrome were collected by searching the electronic literature PubMed, Medline, Embase, and Science Direct databases combining the MeSH heading terms "Hyperparathyroidism jaw tumor syndrome", with the words "Ossifying fibroma" and "CDC73". The collected features were simply assessed and analyzed. Results: The average age was 28.68 years old (age range 10-66), with 12 male and 12 female patients (1:1 M/F ratio). Hyperparathyroidism results from parathyroid adenoma in 16/24 cases (66.666%) and parathyroid carcinome in 5/24 (20.833%). Bone pathology occurred most often in the mandible (16/24 cases; 66.666%), while 5/24 cases were in the maxilla (20.883%) and 3 cases in both (12.5%). In 5/24 cases, ossifying fibroma was the first to occur before hypercalcemia. Genetic mutation of CDC73 were positive in 19/24 cases (79.166%). Conclusion: Since the jaw lesions in Hyperparathyroidism-jaw tumor syndrome could proceed the cardinal signs of hyperparathyroidism, its accurate diagnosis needs to depend on clinical, histological, radiographical, family history and most of all the genetic testing for CDC73 gene.